Sex bias in copy number variation of olfactory receptor gene family depends on ethnicity - Shadravan, Farideh (Frontiers in Genetics, 2013)
Gender plays a pivotal role in the human genetic identity and is also manifested in many genetic disorders particularly mental retardation. In this study its effect on copy number variation (CNV), known to cause genetic disorders was explored. As the olfactory receptor (OR) repertoire comprises the largest human gene family, it was selected for this study, which was carried out within and between three populations, derived from 150 individuals from the 1000 Genome Project. Analysis of 3872 CNVs detected among 791 OR loci, in which 307 loci showed CNV, revealed the following novel findings: Sex bias in CNV was significantly more prevalent in uncommon than common CNV variants of OR pseudogenes, in which the male genome showed more CNVs; and in one-copy number loss compared to complete deletion of OR pseudogenes; both findings implying a more recent evolutionary role for gender. Sex bias in copy number gain was also detected. Another novel finding was that the observed six bias was largely dependent on ethnicity and was in general absent in East Asians. Using a CNV public database for sick children (ISCA) the application of these findings for improving clinical molecular diagnostics is discussed by showing an example of sex bias in CNV among kids with autism. Additional clinical relevance is discussed, as the most polymorphic CNV-enriched OR cluster in the human genome, located on chr 15q11.2, is found near the PWS/AS bi-directionally imprinted region associated with two well-known mental retardation syndromes. As olfaction represents the primitive cognition in most mammals, arguably in competition with the development of a larger brain, the extensive retention of OR pseudogenes in females of this study, might point to a parent-of-origin indirect regulatory role for OR pseudogenes in the embryonic development of human brain. Thus any perturbation in the temporal regulation of olfactory system could lead to developmental delay disorders including mental retardation.